1992
DOI: 10.1152/ajpcell.1992.263.4.c838
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac detection of angiotensinogen and renin: a localized renin-angiotensin system in neonatal rat heart

Abstract: There is increasing evidence that the renin-angiotensin system (RAS) modulates cardiovascular function through both blood-borne and tissue-derived components. The existence of a local RAS has been proposed in the heart based on biochemical and molecular biological studies that identify angiotensinogen and renin. We conducted the present study to determine the chamber localization of angiotensinogen and renin mRNA in neonatal rat heart and whether these components could be identified in cultured cardiomyocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(93 citation statements)
references
References 21 publications
1
90
0
2
Order By: Relevance
“…[3][4][5][6][7][8][9][10] In addition, all components of the RAS are upregulated by pressure overload in the heart. 5,[11][12][13][14][15][16] All these results suggest that the RAS plays a critical role in the development of mechanical stressinduced cardiac hypertrophy. In the present study, however, we have demonstrated that hemodynamic overload fully induces cardiac hypertrophy in genetically engineered mice that lack the AT 1A gene, suggesting that AT 1 -mediated Ang II signaling is not indispensable for the development of pressure overload-induced cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10] In addition, all components of the RAS are upregulated by pressure overload in the heart. 5,[11][12][13][14][15][16] All these results suggest that the RAS plays a critical role in the development of mechanical stressinduced cardiac hypertrophy. In the present study, however, we have demonstrated that hemodynamic overload fully induces cardiac hypertrophy in genetically engineered mice that lack the AT 1A gene, suggesting that AT 1 -mediated Ang II signaling is not indispensable for the development of pressure overload-induced cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 89%
“…8 -10 Many studies have demonstrated that hemodynamic overload activates the tissue RAS in the heart. [11][12][13][14][15][16] mRNA and/or protein levels of renin, 11 ACE, 12,13 angiotensinogen, 5,11,14 and Ang II receptors 15,16 have been reported to be increased in hypertrophied hearts. In addition to these in vivo studies, mechanisms by which mechanical stress induces cardiomyocyte hypertrophy have also been investigated in vitro with cultured cardiac myocytes.…”
mentioning
confidence: 99%
“…However, a related rat skeletal muscle myoblast cell line, L6, has already been shown to express renin. 29 Transcription analysis of the different constructs revealed a complex pattern of 7 potential cis-regulating elements within the first 850 bp of intron I, 5 negative regulatory elements Figure 5. Sequence-specific DNA-binding in rat renin intron I. Protein-DNA complexes were formed with the first 65 nucleotides of intron I partially methylated and endlabelled with 32 P and 293 nuclear extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Myocytes possess the various components of RAS 29,33,34 and generate Ang II. 2,9 -11,29 Conditions of overload in vivo up-regulate this local system 34 and Ang II blockade improves the outcome of ventricular dysfunction and failure of ischemic and nonischemic origin.…”
Section: Adp53m and Myocyte Rasmentioning
confidence: 99%